Penggunaan Bahasa Daerah dalam Jam’iyyah Daerah di Pondok Pesantren Lirboyo Al-Mahrusiyah Kediri - Muhammad Maghfur Ghufron Ggron (Multatuli: Jurnal Bahasa dan Sastra Indonesia, 2025)
The existence of regional languages as a reflection of cultural identity is increasingly threatened by globalization, especially in multicultural environments such as Islamic boarding schools. This study examines the role of Jam’iyyah Daerah (regional organizations) in preserving regional languages at Pondok Pesantren Lirboyo Al-Mahrusiyah Kediri. Employing a qualitative descriptive method, the research involved purposive sampling of santri (students) participating in jam’iyyah activities. Data collection was conducted through in-depth interviews, direct observation, and documentation. The findings reveal that Jam’iyyah Daerah serves as a vital space for santri to use their native languages, thereby maintaining their cultural identity and fostering solidarity. Despite challenges such as the dominance of Indonesian and Javanese languages, as well as limited time, jam’iyyah creates an inclusive environment that naturally encourages the use of regional languages. These activities also boost santri confidence in using their languages beyond pesantren. This research suggests integrating digital tools and expanding community-based models to strengthen language preservation efforts in diverse educational settings.